2015
DOI: 10.1002/ijc.29505
|View full text |Cite
|
Sign up to set email alerts
|

The combined serum levels ofmiR-375and urokinase plasminogen activator receptor are suggested as diagnostic and prognostic biomarkers in prostate cancer

Abstract: This study aimed to assess the applicability of miR‐375 in combination with the soluble urokinase plasminogen activator receptor (suPAR) protein as a diagnostic and/or prognostic biomarker for prostate cancer (PCa) patients. miR‐375 levels by qRT‐PCR and suPAR levels by ELISA were evaluated in serum samples from 146 PCa patients, 35 benign prostate hyperplasia (BPH) patients and 18 healthy controls. Antigen levels of suPAR differed between healthy controls and PCa or BPH patients, whereas miR‐375 levels differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 50 publications
0
34
0
Order By: Relevance
“…Wachet al reported in 2015 that the expression of miR-375 in 146 PCa patients (median: 1.214) was significantly higher than 35 BPH patients (median: 0.360) and 18 healthy controls (median: 0.405) [20]. Haldrup et al reported that miR-375 level was upregulated by 14.66-fold in serum samples from 31 PCa patients when compared to 13 BPH control patients (p=0.009) [21].…”
Section: Discussionmentioning
confidence: 99%
“…Wachet al reported in 2015 that the expression of miR-375 in 146 PCa patients (median: 1.214) was significantly higher than 35 BPH patients (median: 0.360) and 18 healthy controls (median: 0.405) [20]. Haldrup et al reported that miR-375 level was upregulated by 14.66-fold in serum samples from 31 PCa patients when compared to 13 BPH control patients (p=0.009) [21].…”
Section: Discussionmentioning
confidence: 99%
“…miR-375 has been evaluated in this regard. In patients with BPH, no alteration in the plasma level of miR-375 was observed [91].…”
Section: Mir-375mentioning
confidence: 94%
“…Characterization of miRNA involvement likely facilitate predictive and prognostic markers of treatments as well as molecular targets for drug development in this stage and tumor type. miR-375 expression in tissue or circulation has been shown to potentially serve as a biomarker for PC diagnosis or prognosis [1214]. We recently showed significant association of elevated miR-375 levels in plasma with poor overall survival of mCRPC patients [13].…”
Section: Introductionmentioning
confidence: 99%